TEACHERS’ WELLBEING DURING THE COVID-19 PANDEMIC: A REVIEW - Zulkifli, Zaine; Mohd Hashim, Intan Hashimah; Yahaya, Mahathir; Md Said, Fatini (Journal of Human Capital Development (JHCD), 2023)
ABSTRACT The Covid-19 outbreak has added plenty of new pressures for teachers, including difficulties associated with the sudden switch to digital learning. Teachers, as frontline educators, have faced numerous obstacles since the beginning of the Covid-19 epidemic. In recent years, educational environments have placed a greater emphasis on teacher wellbeing. To better understand teacher wellbeing during this crisis and inform strategies that support them, this study examined recent research on teacher wellbeing. Researchers retrieved and analysed studies on teacher wellbeing from Science Direct, Web of Science, and Google Scholar. The findings indicated that teachers experienced a significant level of stress and anxiety. In addition, the study showed the best coping mechanisms for teachers in order to adjust to new circumstances. Finally, recommendations for further research are made, as are the implications. Keywords: wellbeing, pandemic, Covid-19, teacher